The Effect of Fillers on the Chemical, Mechanical and Dielectric Properties of Polyvinyl Chloride Composites (Baghdad Science Journal, 2015)
The compounding of polyvinyl chloride (PVC) with two types of fillers and some additives were studied for the manufacturing of acid resistant tile. Various concentrations of two types of fillers namely; calcium carbonate and recycled glass powder were used along with different additives generally categorized as plasticizers, stabilizers, and lubricants were mixed in the standard concentration unit parts per hundred resins (phr) with the PVC as base polymer. The effects of filler materials on acid resistant towered different acids like sulphuric, nitric and hydrochloric at different concentration were studied. Samples which passed the test were further checked for dielectric strength and mechanical properties. It was found that the recycled glass powder is very suitable filler for preparing PVC composites materials for flooring tile, where most samples undergo negligible change in weight and maintained its shape and flexibility during the acid resistant test.